Aetiological Approach to Patient with Non- Specific Chronic Cough (TAJ: Journal of Teachers Association, 2018)
Chronic cough is a problem commonly encountered by the practicing physicians. Definitive treatment depends upon identifying the cause of cough4.To develop an appropriate algorithm for diagnosis of non-specific chronic cough a Prospective case-control study was carried out in Asthma Centre,NIDCH, Mohakhali, Dhaka during the period of January,2000 to December,2001. Eighty two patients with history of cough for 3 weeks or more duration were taken in group A.The ages ranged from 11 to 68 years with mean age 35.5 ± 12.0 years. There were 43 males and 39 females. Equal number of subjects having no cough were taken as control (group B).The age of control subjects ranged from 11 to 68 years with mean age 35.6 ± 11.9 years. Diagnosis was made in all patients. PNDS was found in 41(50%), PNDS with cough variant asthma in 19(23.2%),cough variant asthma alone in 10(12.2%),GERD singly in 2(2.4%).In control group, only 5 (6.1%) persons were diagnosed as PNDS who had almost all features of PNDS except cough. In this studuy, PNDS alone and in combination with cough variant asthma were common causes of chronic cough.TAJ 2012; 25: 1-7